GENERALIZED MATHEMATICAL MODEL OF MOVEMENT OF A COMBINED SOWING MACHINE-TRACTOR UNIT - Yaroshenko, P. M.; Arendarenko, V. M. (Scientific Progress & Innovations, 2020)
The quality of technological operations depends on the character of machine movement and, above all, on how the stability of operated movement is ensured. Even at a slight external action that causes the ma- chine with elastic wheels to deviate from the original trajectory, it is possible to return to it only through the efforts of farm machine operator to the functioning system. The deviation of a wheeled vehicle from prede- termined direction of movement can be a result of the action of external forces on elastic wheels, turns of directed wheels within spacing and deformation of steering parts, as well as inaccuracies in the work of farm machine operator. In this regard, ensuring guided straight movement of serial models of 30 kN class wheeled tractors is of great importance. Increasing the operating speeds of power-intensive tractors requires considerable effort and energy of farm machine operator to drive it. Thus, increasing the stability of com- bined sowing units’ movement is an important scientific-applied task. The main aims of this work are to de- velop and improve theoretically generalized mathematical movement model of the sowing combined ma- chine-tractor unit in the technological sowing process on the basis of 30 kN tillage tractor with a frame structure, as well as to analyze the influence of the dynamics of combined sowing technology components in rear tractor seeder while conducting technological process. To develop a mathematical model of a combined sowing unit movement, we will present it in the form of a three-element model and it will be used to calculate the second-order Lagrange equation. In making the mathematical model, six assumptions were adopted, which made it possible to simplify the solution of the problem, as well as to reject the factors that complicat- ed the development of the mathematical model and practically do not affect the course of calculations. As a result of the work, it has been found that studying the stability of the unit movement can be performed on the basis of a three-mass model, which has linear characteristics of external resistances, without taking into ac- count the slipping of propellers on the support surface. On the basis of the conducted theoretical researches it has been established that the obtained mathematical model enables to determine the limits of stability of the combined unit movement during the sowing process.